Flooded through the back door: Firm-level effects of banks' lending shifts - Oliver Rehbein (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
I show that natural disasters transmit to firms in non-disaster areas via their banks. This spillover of non-financial shocks through the banking system is stronger for banks with less regulatory capital. Firms connected to a disaster-exposed bank with below median capital reduce their employment by 11% and their fixed assets by 20% compared to firms in the same region without such a bank during the 2013 flooding in Germany. Relationship banking and higher firm capital also mitigate the effects of such negative cross-regional spillovers.
urn:nbn:de:101:1-201802121789
Keywords: E24; E44; G21; G29; 330; natural disaster; real effects; shock transmission; bank capital